An assessment of a non-destructive magneto-optical imaging technique for the recovery of laser engraved marks from steel plates and firearm components - Henwood, Bailey J.; Helliker, Aimee; Hazael, Rachael; Hewins, Katherine (Elsevier, 2023)
The International Tracing Instrument (ITI) is a document adopted by United Nations Member States in 2005, which outlines challenges faced in the tracing of illicit weapons and offers suggestions to increase the success of tracing operations. A key provision of the ITI states that serial numbers must be recoverable if obliterated. This research, therefore, investigates two methods of recovering laser engraved marks on steel, due to the increase in firearms manufacturing relying on lasers to apply critical markings. This work uses 20 steel plates (CR4 grade), 6 AK-pattern rifle top covers, and a steel pistol slide to investigate the potential for visualising laser engraved marks. All samples had marks applied using a BWM-30F Fibre laser marking machine, in addition to any original manufacture’s stamped marks on the pistol. All marks were removed using a grinding belt (plates) and a Dremel® rotary tool (slide and top covers) to average depths of 1200 µm (stamped) and 240 µm (laser engraved). Recovery of the marks was attempted using two techniques to compare the two techniques in their ability to recover laser engraved marks; Regula Forensics® Eddy Current Recovery kit, followed by traditional Fry’s reagent. Both recovery techniques recovered 100 % (n = 6) of the stamped characters on the pistol slide, and 0 % (n = 509) of the laser engraved characters on the pistol, top covers and steel plates. Recommendations are made for forensic firearms examiners to avoid attempting the recovery of laser engraved marks using Fry’s reagent to preserve the integrity of evidence. It is also suggested that manufacturers avoid laser engraving unique identifying marks on firearms, and to use more permanent methods, such as stamping, to remain compliant with politically binding documents such as the ITI.
Keywords: Firearms; C4 steel; Fry’s reagent; Eddy current; Non-destructive recovery; International Tracing Instrument